The use of T-cells with chimeric antigen receptor (CAR-T) in combination with chemotherapy and radiotherapy for the treatment of solid tumors - M. R. Khaliulin; R. N. Safin; M. A. Kunst; E. R. Bulatov (Успехи молекулярной онкологии)
The introduction of chimeric antigen receptor (CAR) T-cell therapy has revolutionized the treatment of hematological diseases, particularly in combating blood cancer. The success of this cell therapy approach has led to the development of approximately seven commercial CAR-T based drugs. However, the application of CAR-T therapy for solid tumors has proven to be less effective due to challenges such as the varied antigens in solid tumors, an immunosuppressive tumor environment, limited immune cell infiltration, reduced CAR-T cell activity and toxicity issues. To solve these problems, scientists are making efforts to improve and improve the methods of treatment of solid tumors. Chemotherapy is the standard treatment for a large number of malignant neoplasms. It is also used before starting cell therapy for lymphodepletion and better engraftment of injected CAR-T cells. It has been shown that chemotherapy can reduce the immunosuppressive effect of the tumor microenvironment, destroy the stroma, and promote better infiltration of the tumor by CAR-T cells, improving their survival, persistence, cytotoxicity, and influencing the metabolism of immune cells inside the tumor. The effectiveness of combining chemotherapy and CAR-T cell therapy relies on various factors such as tumor type, dosage, treatment schedule, CAR-T cell composition, and individual biological traits. Similarly, radiation therapy can enhance tumor cell vulnerability to specific treatments while also supporting tumor cell survival.In this review, we discuss the use of CAR-T therapy to combat solid tumors, regarding the challenges of treating solid tumors, ways to overcome them, and also touch upon the possibility of using combination treatments to improve the effectiveness of cell therapy.